Peran Petugas Kesehatan Terhadap Konsumsi Tablet Zat Besi (Fe) Dengan Kejadian Anemia Pada Ibu Hamil Di Wilayah Kerja Puskesmas Kota Bogor - Fika Lestari; Ratna Dewi; Kurniati Nawangwulan; Yusnita Yusfik; Eny Retna Ambarwati; Adity Dwi Treasa; Sri Wahyuni (Journal on Education, 2025)
Anemia in pregnant women can be caused by an increase in oxygen demand so that erythropoietin production in the kidneys also increases. This causes red blood cells (erythrocytes) to increase by 20-30%. This increase is not comparable to the progressive increase in plasma volume, which is 40-45%, so that a hemodilution process (blood thinning) occurs which causes a decrease in Hb concentration. This research method is an analytical survey with a Cross-Sectional research design, namely research on the relationship between two variables in a condition or group of individuals. The results of the Chi-Square test obtained a p Value = 0.020 ≤ α (0.05), this shows that there is a relationship between the role of health workers and the consumption of Fe tablets. The conclusion is that as health workers, they can increase their active role in providing counseling, information counseling and education to pregnant women and their families about consuming Fe tablets and especially to pregnant women to consume Fe tablets during pregnancy.